2013
DOI: 10.1063/1.4801401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface periodic grating on film bulk acoustic resonator structures to spurious transverse resonances

Abstract: Articles you may be interested inAdvanced numerical technique for analysis of surface and bulk acoustic waves in resonators using periodic metal gratings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…These results indicate that the slotted top electrode is effective for controlling propagation of lateral modes, similar to the grating placed on the top electrode [15].…”
Section: Resonance Characteristicsmentioning
confidence: 88%
See 2 more Smart Citations
“…These results indicate that the slotted top electrode is effective for controlling propagation of lateral modes, similar to the grating placed on the top electrode [15].…”
Section: Resonance Characteristicsmentioning
confidence: 88%
“…a series of spurious resonances is seen at frequencies above f r . as explained in [15], they are caused by the lamb mode (s 1 ) propagation, which occurs at frequencies above the main resonance in the Mo/Zno/Mo structure. Fig.…”
Section: Resonance Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…It plays a major role in suppressing the transverse resonances. Liu et al [6 ] reported that a transverse‐free fundamental resonance is obtained provided that period of grating and thickness is set so that the stop band covers the range of frequencies where the transverse mode resonances occur. This technique is effective to suppress the transverse resonances and improve the quality factor at the cost of reducing the effective electromechanical coupling coefficient [7 ].…”
Section: Introductionmentioning
confidence: 99%
“…© 2020 The Japan Society of Applied Physics Supplementary material for this article is available online O ptical interferometry techniques have been widely studied due to direct, non-contact measurements of out-of-plane vibration fields which provide information for the design and performance of micro-structures. [1][2][3][4][5][6][7][8][9][10][11] Among these techniques, full field interferometers [12][13][14][15][16][17][18] are faster than scanning laser interferometers [19][20][21][22][23][24][25][26][27][28][29] in obtaining the whole vibration image. The frequency range and the amplitude range of these two types of interferometers are different.…”
mentioning
confidence: 99%